Development of Halide Perovskite Single Crystal for Radiation Detection Applications - Pan, Wanting; Wei, Haotong; Yang, Bai (Frontiers in Chemistry, 2020)
Nowadays, low-cost perovskite single crystals have attracted intensive attention due to their excellent optoelectronic properties and improved stability compared to polycrystalline films for various applications like solar cells (Kojima, Teshima, Shirai, & Miyasaka, 2009; Lee, Teuscher, Miyasaka, Murakami, & Snaith, 2012; Sahli et al., 2018; Tsai et al., 2016), lasers (Gu et al., 2016; Veldhuis et al., 2016), radiation detection (Kim et al., 2017), and so on. The unique optoelectronic properties and low-cost solution grown processes for large dimensional size single crystals also make them greatly suitable for radiation detection. In this review, we summarized various synthesis methods of perovskite single crystals, and highlighted the relationship between detectors performance with crystals synthesis processes, crystals composition, passivation techniques, and devices structure. The advantages and limitation of halide perovskite as radiation detector candidate will be discussed in detail, and corresponding future development trends can be expected by overcoming the current obstacle (Boyd, Cheacharoen, Leijtens, & McGehee, 2019; Leijtens, Bush, Prasanna, & McGehee, 2018) such as ions migration (Eames et al., 2015), stability (Bai et al., 2019; Liu et al., 2019), stability, and etc.